Augmented nested coprime array with displaced subarrays design achieving reduced mutual coupling. Issue 4 (3rd April 2023) - Yu, Weichuang; He, Peiyu; Pan, Fan; Qiu, Da; Fang, Ancheng; Xu, Zili
ABSTRACT: Mutual coupling effect and degrees of freedom (DOFs) play a crucial role in the sparse array design. In this paper, we judiciously configure the dense subarray and sparse subarray of the nested coprime array with displaced subarrays (NCADiS) to obtain an improved NCADiS (INCADiS). Then, the dense subarray of the INCADiS is split into two parts and rearranged on the left and right sides of the sparse subarray of the INCADiS to structure an augmented nested coprime array with displaced subarrays (ANCADiS). We also derive the closed-form expressions for the element locations and the number of uniform DOFs (uDOFs) of the ANCADiS configurations with any number of elements. The proposed array configuration has the same uDOFs as the INCADiS and the prototype optimised NCADiS (PNCADiS), and at the same time achieves reduced mutual coupling. Some theoretical properties are proved, and numerical simulations are included to verify the superiority of the proposed configuration.